Cover Design as Value Co-Creation: Its Impact on Consumer Purchase Intention Within the Framework of Service-Dominant Logic - Rudi Suprianto; Sandy Wahyudi; Bisma Jatmika Tisnasasmita; Teofilus Teofilus; Hastuti Naibaho (Publikasi Indonesia, 2026)
The rapid development of digital technology has transformed consumer behavior, including learning activities. Although the use of digital media in education continues to increase, notebooks remain an essential learning tool for students. This condition encourages manufacturers to focus not only on product functionality but also on visual design as a means of enhancing consumer appeal. This study aims to examine the effects of cover design and product quality on consumers' purchase intention toward notebooks, with consumer engagement and promotion serving as mediating variables. A quantitative research approach was employed using a survey of 400 senior high school students in East Java, Indonesia, selected through purposive sampling. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4 software. The findings reveal that cover design does not have a direct effect on purchase intention but has a positive and significant effect on consumer engagement and promotion. Furthermore, consumer engagement fully mediates the relationship between cover design and purchase intention. Product quality and promotion also have positive and significant effects on purchase intention. These findings reinforce the Service-Dominant Logic (SDL) perspective, which argues that product value is created not only through physical attributes but also through consumer engagement in the process of value co-creation. This study contributes theoretically by extending the application of SDL to the context of low-involvement products. It also provides managerial implications for notebook manufacturers by recommending consumer insight-driven design strategies tailored to different market segments, supported by effective promotional activities and consistent product quality.